Proposing a mini-games program and its effect on improving some basic motor skills (running, throwing, and jumping) for a child (6-7) years old - BOUKHALFA, ABDELKADER (sports creativity, 2025)
This study aimed at using a programme suggested with small games to improve some basic motor skills for pupils of 6-7 years in the primary stage, The benefit of this lies in finding a program that develops the child's abilities to acquire the most important skills and basic movements, Our study population is represented by pupils in the first year of primary school (6-7 years) and the study sample included 31 pupils who were deliberately chosen, Where we pre-measured the pupils' abilities in running, jumping, and throwing skills based on Johnson's test of motor skills, then we prepared a program consisting of a group of mini-games that improve these skills, and then we measured my dimension with the same test. Through this study, we found that there are statistically significant differences between the pre and post tests in favour of the post test in improving the skills of running and jumping, as well as a slight, non-statistically significant improvement in the skill of throwing.